Revisiting an English extensive reading program in a low “commercial” resources setting - Christine Manara (Universitas Katolik Indonesia Atma Jaya, 2019)
This paper is a teacher’s critical reflection on the implementation of an Extensive Reading (ER) Program in a teaching context with low resources of commercial graded readers. The paper presents the teacher's dialogue with the ten principles for ER in designing and implementing an ER program. During this process, there are several issues related to the education system and culture as well as the availability of L2 resources. The paper firstly starts with the initial reflection on the previous practices on teaching English reading at a tertiary level to identify the problems. Next, the rationale for initiating an Extensive Reading Course is laid out. Then, samples of teaching activities implemented during the program are presented. Lastly, reflective evaluation of the program is presented with several contextual and pedagogical considerations in working at a low English “commercial” resources context.